2017
DOI: 10.1016/j.rpor.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric image-guided highly conformal radiotherapy of the prostate bed: Toxicity analysis

Abstract: a b s t r a c tAim: To evaluate toxicity of high conformal image-guided radiotherapy of the prostate bed.Background: Radiotherapy of the prostate bed has a pivotal role in the post-operative and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Moreover, failure after SRT occurs in 82% of patients with a pre-SRT value ≥ 1.5 ng/ml [ 5 8 ]. Thus, local burden of disease negatively affects prognosis of these patients, and therapeutic ratio of conventional SRT may be further worsened by a rate of late grade ≥ 2 GI and GU adverse events reported in the literature, ranging between 3.4 and 18% [ 9 11 ]. In this setting, dose-escalated treatment may achieve better disease control [ 12 ].…”
Section: Purpose/objectivementioning
confidence: 99%
“…Moreover, failure after SRT occurs in 82% of patients with a pre-SRT value ≥ 1.5 ng/ml [ 5 8 ]. Thus, local burden of disease negatively affects prognosis of these patients, and therapeutic ratio of conventional SRT may be further worsened by a rate of late grade ≥ 2 GI and GU adverse events reported in the literature, ranging between 3.4 and 18% [ 9 11 ]. In this setting, dose-escalated treatment may achieve better disease control [ 12 ].…”
Section: Purpose/objectivementioning
confidence: 99%
“…Recently, Palumbo et al [20] reported that statins were an independent factor associated with the reduction of acute GI toxicity in 195 patients treated with IMRT for localized PCa. The protective effect of ADT on the intestinal tissue, which has been demonstrated in animal models [21] as well as in clinical studies [22][23][24], could depend on the reduction of radiation-induced cytokines and pro-inflammatory molecules (i.e., IL-6, NFkB, TGFβ) [21] within the irradiated rectal wall in patients under androgen deprivation. We identified anticoagulants and antiaggregants as clinical variables associated with acute GU toxicity, but we have to consider that anticoagulant therapy itself is a risk factor for urinary complaints and hematuria.…”
Section: Discussionmentioning
confidence: 99%
“…In a French retrospective study [25], these agents significantly affected late GU toxicity in 965 patients treated with EBRT for localized PCa. Even though the relationship between radiation-induced toxicity and anticoagulants is not clear, some reports showed that their use could be associated not only with GU but also with rectal toxicity [22,24,26] in patients undergoing radiotherapy for localized PCa. About oncologic outcomes, in our analysis clinical prognostic factors (D' Amico risk class and ISUP grade) are important tools in detecting the risk of disease progression in localized PCa patients.…”
Section: Discussionmentioning
confidence: 99%
“…Rectal bleeding as a side-effect after prostate cancer radiation therapy, PCRT, is frequently reported and the extent has been shown to be related to absorbed dose to the rectum [ 1 , 2 ]. However, most data are from primary PCRT while there is limited information on the risk of rectal bleeding in the postoperative setting, delivered by salvage radiation therapy, ST [ 3 , 4 ]. Since ST is a rescue after radical prostatectomy in prostate cancer and the only curative treatment option when there is a PSA-relapse after surgery, knowledge of curability and side-effects seem crucial.…”
Section: Introductionmentioning
confidence: 99%